Beta Thalassaemia Mutations in Malays: a simplified cost-effective strategy to identify the mutations - George, E.; Teh, L.K.; Rosli, R.; Lai, M.I.; Tan, J.A.M.A. (2012)
Background/Aims: Beta (Î²)- thalassaemia is a public health problem in Malaysia. The carrier rate is estimated to be 4.5 by micro-mapping studies particularly among Malays who comprise 53.5 of the population in Malaysia (1). The common diagnostic method in Malaysia for mutation detection is by amplification refractory mutation system (ARMS). It allows single mutation detection in each reaction but is labour intensive and time consuming when many mutations need to be identified. The purpose of this study was to develop a diagnostic tool for effective mutation detection of beta thalassaemia in Malay patients and compare its efficacy with ARMS-PCR, the current method in use. Methods: Reverse dot blot hybridization (RDBH) technique was incorporated in the development of two strip assays RDBH-Strip M(6) and RDBH-Strip C(6) to identify common beta thalassaemia mutations in the Malays. The panels of selected mutations were based on the mutation frequencies in Malaysia reported in previous studies. RDBH-Strip M(6) was applied as step 1 and RDBH-Strip C(6) was applied as step 2 for unidentified mutations. The strips were validated with the gold standard method, ARMS-PCR. Results: One hundred and thirty seven Malay patients with 274 alleles were studied. In Step 1 mutation detection, 238 alleles (86.9%) were identified in 119 of patients by RDBH-Strip M(6). Step 2 resulted in a further detection of 20 alleles in another 10 patients by RDBH-Strip C(6). The combination of both strips resulted in the identification of 258 alleles in 129 (94.6%) of 137 Malay patients. The strip assays were 100% sensitive and specific when compared with ARMS-PCR method. Conclusion: Two strip assays utilising the RDBH technique were developed to identify common Î²-thalassaemia mutations in Malays. The RDBH Strip M(6) identified 86.9% of the mutations and the RDBJ-Strip C (6) detected further 7.3% alleles. This two step strategy was found to be rapid and cost effective for the direct diagnosis of Î²-thalassaemia mutations in the Malays. The remaining unidentified mutations would require DNA sequencing. It can serve as a specific molecular diagnostic tool for effective diagnosis of Î²-thalassaemia mutations in this ethnic group.